The Nuremberg Military Tribunals and the origins of international criminal law - Heller, Kevin Jon, author (Oxford ; New York : Oxford University Press, 2011)
"This book provides the first comprehensive legal analysis of the twelve war-crimes trials held in the American zone of occupation between 1946 and 1949, collectively known as the Nuremberg Military Tribunals (NMT). The judgments these Tribunals produced have played a critical role in the development of international criminal law, particularly in terms of how courts currently understand genocide, crimes against humanity, and the crime of aggression. The trials are of tremendous historical importance, because they provide a far more comprehensive picture of Nazi atrocities than the main Nuremberg Trial (IMT). The IMT focused exclusively on the 'major war criminals'-the Goerings, the Hesses, the Speers. The NMT, by contrast, prosecuted doctors, lawyers, judges, industrialists, bankers-the private citizens and lower-level functionaries whose willingness to take part in the destruction of millions of innocents manifested what Hannah Arendt famously called 'the banality of evil'. This book starts by tracing the history of the NMT. It then discusses the law and procedure applied by the NMT, with a focus on the important differences between Control Council Law No. 10 and the Nuremberg Charter and on the protection of the defendants' right to a fair trial. The third section, the heart of the book, provides a systematic analysis of the NMT's jurisprudence. It covers Law No. 10's core crimes, crimes against peace, war crimes, and crimes against humanity, as well as the crimes of conspiracy and membership of a criminal organization. This section also analyzes the general principles of liability that the Tribunals applied and on the defenses they did -and did not- recognize. The final section of the book deals with the aftermath of the trials and their historical legacy"--
Includes bibliographical references (p. [487]-492) and index.
Keywords: Nuremberg Trial of Major German War Criminals, Nuremberg, Germany, 1945-1946.; War crime trials -- Germany -- Nuremberg -- History -- 20th century; International crimal law -- History